Time domain electromagnetics - Rao, Sadasiva (Academic Press series in engineering., 1999)
Time Domain Electromagnetics deals with a specific technique in electromagnetics within the general area of electrical engineering. This mathematical method has become a standard for a wide variety of applications for design and problem solving. This method of analysis in electromagnetics is directly related to advances in cellular and mobile communications technology, as well as traditional EM areas such as radar, antennas, and wave propagation. Most of the material is available in the research journals which is difficult for a non-specialist to locate, read, understand, and effectively use for the problem at hand. * Only book currently available to practicing engineers and research scientists exclusively devoted to this subject * Includes contributions by the world's leading experts in electromagnetics * Presents the most popular methods used in time domain analysis are included at one place with thorough discussion of the methods in an easily understandable style * In each chapter, many simple and practical examples are discussed thoroughly to illustrate the salient points of the material presented * All chapters are written in a consistent style that allows the book to be of use for self-study by professionals as well as for use in a graduate-level course in electrical engineering.